Core-Shell Microgels with Switchable Elasticity at Constant Interfacial Interaction - Seuss, Maximilian; Schmolke, Willi; Drechsler, Astrid; Fery, Andreas; Seiffert, Sebastian (ACS Applied Materials and Interfaces, 2016)
Hydrogels based on poly(N-isopropylacrylamide) (pNIPAAm) exhibit a thermo-reversible volume phase transition from swollen to deswollen states. This change of the hydrogel volume is accompanied by changes of the hydrogel elastic and Young's moduli and of the hydrogel interfacial interactions. To decouple these parameters from one another, we present a class of submillimeter sized hydrogel particles that consist of a thermosensitive pNIPAAm core wrapped by a nonthermosensitive polyacrylamide (pAAm) shell, each templated by droplet-based microfluidics. When the microgel core deswells upon increase of the temperature to above 34 °C, the shell is stretched and dragged to follow this deswelling into the microgel interior, resulting in an increase of the microgel surficial Young's modulus. However, as the surface interactions of the pAAm shell are independent of temperature at around 34 °C, they do not considerably change during the pNIPAAm-core volume phase transition. This feature makes these core-shell microgels a promising platform to be used as building blocks to assemble soft materials with rationally and independently tunable mechanics.
CRIS-Team Scopus Importer:2023-03-20
Keywords: AFM; core-shell microgels; elasticity; interfacial interaction; thermoresponsivity